Development and applications of graduate outcome-based curriculum for basic medical education - Chen, Guang; Wang, Hongmei; Zhou, Lingling; Yang, Jingjin; Xu, Linglong; Liang, Yong (Frontiers in Medicine, 2024)
Introduction: Outcome-based education (OBE) leads to revolutionary change in medical education, but each medical school is acknowledged to develop suited framework based on specific positioning, educational philosophy and expected outcomes. Methods: Based on the graduate outcomes of basic medical education in China released by Working Committee for the Accreditation of Medical Education (WCAME) which officially recognized by World Federation for Medical Education (WFME), Taizhou University re-documented the overall organization of the curriculum and classified the courses as “Crucial, Supporting and Associated (CSA)” categories to connect the graduate outcomes and course objectives. Results: We redefined the standard for graduates in Taizhou University Medical School including 34 items in four domains and redesigned the curriculum with 76 courses classified as CSA. Empirical data reveals a substantial improvement in students' performance on Standardized Competence Test for Clinical Medicine Undergraduates in China (SCTCMU) by implementing the CSA system between 2022 and 2023. Notably, in 2023, Taizhou University's students achieved pass rates more than 20 percentage points higher than the national average, demonstrating a profound and unprecedented impact. Conclusions: The CSA classification system provides a notably clear and structured framework for categorizing courses based on their direct or indirect relevance to educational objectives, which provides clarity to educators and empowers students with a more purposeful approach to their studies.